2016
DOI: 10.1002/pc.24125
|View full text |Cite
|
Sign up to set email alerts
|

Thermal oxidation aging of polydicyclopentadiene and composites

Abstract: The thermal aging and oxidation behavior of polydicyclopentadiene and composites was investigated, and the effects on thermal and mechanical properties were determined. Thermal and mechanical properties were measured by dynamic mechanical analysis, static tensile test, and short-beam shear tests. Diffusion limited oxidation was observed and oxidation was limited within the surface region (100 mm) of the sample. Single-fiber push-out test methodology was developed to directly measure the bond strength of fiber-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 35 publications
0
14
0
Order By: Relevance
“…The concentrations of carbonyls generated by oxidation were calculated using the Beer-Lambert equation with a molar absorptivity of 300 mol l À1 cm À1 [4] at 1710 cm À1 . The double bond concentration methods will be detailed later.…”
Section: Fourier Transform Infrared Spectroscopymentioning
confidence: 99%
See 2 more Smart Citations
“…The concentrations of carbonyls generated by oxidation were calculated using the Beer-Lambert equation with a molar absorptivity of 300 mol l À1 cm À1 [4] at 1710 cm À1 . The double bond concentration methods will be detailed later.…”
Section: Fourier Transform Infrared Spectroscopymentioning
confidence: 99%
“…The final kinetic model appears to be suitable at least in the domain of moderate degrees of conversion and allows the extent of PDCPD degradation to be predicted with time, temperature and external oxygen pressure as input parameters. The case of stabilized PDCPD should now be addressed to get closer to practical cases [4,5,6,29].…”
Section: T( C)mentioning
confidence: 99%
See 1 more Smart Citation
“…This reaction leads to the formation of a new chemical bond and so an increase in the crosslink density of the polymer. Finally, based on literature, it appears that oxidation leads to large changes in mechanical behavior [1,11]. However, all these tests were performed on thick samples, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Organic-inorganic hybrid films represent a class of new advanced materials that combine the flexibility and processability of organic polymers with superior mechanical and thermal stability of inorganic phase. Much research was reported on the fabrication of PEEK nanocomposites by using low-cost conventional techniques such as extrusion and compression molding [17][18][19][20]. To produce composites exhibiting improved properties, different strategies were used to achieve a good dispersion of nanofiller within the polymer matrix, such as ultrasonication, ball milling, wrapping in compatibilizing agents, polymer functionalization, and covalent grafting.…”
Section: Introductionmentioning
confidence: 99%